Transcriptome Profile of Rat Adrenal Evoked by Gonadectomy and Testosterone or Estradiol Replacement - Jopek, Karol; Celichowski, Piotr; Szyszka, Marta; Tyczewska, Marianna; Milecka, Paulina; Malendowicz, Ludwik K.; Rucinski, Marcin (Frontiers in Endocrinology, 2017)
Sex differences in adrenal cortex structure and function are well known in different species. In the rat they are manifested as larger adrenal cortex and higher corticosterone secretion by females compared with males. These sex differences depend, among others, on functioning of the hypothalamo-pituitary adrenal axis (HPA). In this aspect, it is widely accepted that testosterone exerts an inhibitory and estradiol stimulatory effect on the said axis. The molecular bases of these sex related differences are poorly understood. Therefore we performed studies aimed to demonstrate the effect of testosterone and estradiol on the expression of differentially regulated genes in rat adrenal gland. The classical method applied in the study - gonadectomy and gonadal hormone replacement - allows obtaining results suggesting a physiological role of the tested hormone (testosterone or estradiol) in the regulation of the specific genes. Adult male and female rats were either gonadectomized or sham operated. Half of orchiectomized rats were replaced with testosterone while ovariectomized ones with estradiol. Transcriptome was identified by means of Affymetrix® Rat Gene 2.1 ST Array. Differentially expressed genes were analyzed by means of DAVID web-based bioinformatic tools and confirmed by means of Gene Set Enrichment Analysis (GSEA). For selected genes validation of the results was performed using QPCR. Performed experiments have provided unexpected results. Contrary to expectations, in orchiectomized rats testosterone replacement stimulates expression of numerous genes, mainly those associated with lipids and cholesterol metabolism. However, in ovariectomized animals estradiol replacement inhibits the expression of genes, mainly those involved in intracellular signaling pathways.The physiological relevance of these findings awaits further research.